Effects of metaraminol bitartrate on intraocular pressure in dogs under halothane anesthesia - Bolzan, Aline Adriana [UNESP]; Laus, José Luiz [UNESP]; Nunes, Newton [UNESP]; De Andrade, Alexandre Lima [UNESP] (Wiley, 1998)
The effects of metaraminol bitartrate on intraocular pressure (IOP) were studied in dogs anesthetized with halothane. Forty-five healthy, adult, mixed-breed dogs, of both sexes, were divided into three groups of 15 dogs each (GI, GII and GIII) and maintained under general anesthesia with halothane after tranquilization with levomepromazine and induction with thiopental. Saline (0.9%) was administered intravenously (IV) to GI through continuous infusion, at a velocity of 0.125 mL kg -1 min -1. GII and GIII received metaraminol 0.004% IV, at a dose of 5 μg kg -1 min -1, at 0.125 mL kg -1 min -1 and at a dose of 2 μg kg -1 min -1, at 0.06 mL kg -1 min -1, respectively. IOP was measured by applanation tonometry (Tono-Pen) before and during anesthesia. Results showed that IOP decreased in GI, increased in GII, and remained at basal levels in GIII. Continuous infusion of metaraminol at 2 μg kg min -1 maintained IOP at pretest levels, while infusion at 5 μg kg -1 min -1 produced an elevation of IOP.
Keywords: Dogs; Halothane; Intraocular pressure; Metaraminol bitartrate